Implementasi Manajemen Berbasis sekolah - Siti Maratussholihah; Nadialiana; Syafaatul Habib (Fakultas Tarbiyah dan Keguruan dan UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
The purpose of this research is to examine how School-Based Management (SBM) is implemented in Islamic educational institutions and Determine the elements influencing its success and the obstacles encountered in the implementation of SBM. In addition, this journal also provides strategic recommendations to optimize the implementation of SBM in the Islamic education environment. The analysis was carried out by examining the existing literature on SBM in the context of Islamic education. Emphasis is placed on supporting factors such as leadership, community participation, and government policy support. In addition, emerging challenges, such as resistance to change, resource limitations, and organizational culture conflicts, are also analyzed to get a clearer picture from the possible obstacles. The findings of the analysis show that strengthening leadership capacity, developing managerial training for educators, and increasing collaboration between educational institutions and local communities are the main strategies that can optimize the implementation of SBM. By employing this strategy, it is anticipated that SBM can be applied successfully improving educational standards in Islamic institutions, while contributing positively to the growth of students' character and competencies.